Perjanjian Paket Wisata antara Fakultas Hukum Universitas Wijayakusuma Purwokerto dengan Biro Perjalanan Wisata CV Putra Wisata - S. Suryati; Aris Priyadi; Bing Waluyo (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2019)
Article 1 of Law No. 10 Years 2009, tourism: travel activities carried out by a person or group of people by visiting certain places for recreational purposes, personal development, or studying the uniqueness of tourist attractions visited in the interim period. Agreement on land travel using land vehicles in the form of unknown buses in Book III of the Civil Code and KUHD. The purpose of this study is to find out the legal responsibilities of CV Putra Wisata as a travel agency when there is a default. The research method uses normative juridical, by synchronizing the legal principles of the agreement with the legislation in force in Indonesia. The data obtained is analyzed qualitatively. The conclusion is that there are several possible forms of responsibility as a Tourist Travel Bureau when there is a default, namely: keep on carrying out travel without compensation or cancellation of the agreement without or with compensation.Keyword: Legal Responsibility, Agreement, Tour Package